2022
DOI: 10.3389/fpls.2022.970023
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the formation of diverse petal colors of Lagerstroemia indica by integrating the data from transcriptome and metabolome

Abstract: Lagerstroemia indica has great economic value due to its ecological, medicinal, and ornamental properties. Because its bloom color is one of the most essential characteristics, research into its color development is a hot topic. In this study, five representative colored cultivars were chosen, each representing a different color, such as white, red, pink, violet, and purple. Fully bloomed flowers were used to detect flavonoids in the petals. Anthocyanin is the main factor for the color formation of L. indica. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Furthermore, delphinidin 3- O -glucoside, cyanidin 3- O -glucoside, petunidin 3- O -glucoside, and peonidin 3- O -glucoside also showed a decreasing trend [ 24 ]. Similar investigations were also reported [ 62 , 63 ]. Therefore, our metabolomics analysis once again proved the importance of anthocyanin content in petal coloration.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, delphinidin 3- O -glucoside, cyanidin 3- O -glucoside, petunidin 3- O -glucoside, and peonidin 3- O -glucoside also showed a decreasing trend [ 24 ]. Similar investigations were also reported [ 62 , 63 ]. Therefore, our metabolomics analysis once again proved the importance of anthocyanin content in petal coloration.…”
Section: Discussionsupporting
confidence: 90%
“…Dihydromyricetin is a precursor in the synthesis of delphinidin, petunidin and malvidin. Previous research has suggested that delphinidin, petunidin and malvidin can endow plant tissues and organs with a purple color, and the gene, F3′5′H , is frequently associated with purple color formation [ 37 , 38 ]. In the present work, we detected that the gene, F3′5′H ( MsG0380013382.01 , Log 2 fold-change value = 1.80), is significantly upregulated in purple flowers compared to cream flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis is a post-genomic technology designed to provide a comprehensive profile of all metabolites (estimates at least 200,000) in a typical plant and represents an important branch of systems biology [ 39 ]. Via metabolomic analysis, many researchers have deeply studied the differences in flavonoid metabolites in crops, fruits, and flowers under different conditions to provide new insights into genetic breeding [ 40 , 41 , 42 , 43 , 44 ]. In this study, metabolomics technology was used to determine and analyze the metabolite content of different chrysanthemum cultivars.…”
Section: Discussionmentioning
confidence: 99%